An Analysis of Compound Words in The Novel "The Fault In Our Stars" - Nurafni, Selviana; Baskoro, B.R Suryo (TRANSFORMATIKA, 2023)
This study discusses compound words in English novels and aims to find out what types of compound words and which types of compound words are used the most in the novel. The method used in this research is descriptive analysis with a qualitative approach (Miles, Huberman Saldana, 2018). Data collection used documentation which the source is from a novel by John Green entitled The Fault in Our Stars. Data analysis was based on Yule (2016). The results obtained that there are 207 data consisting of two types of compound words, namely endocentric with 152 data (73%) and exocentric with 55 data (27%) which are formed from the word compound nouns (N+N, A+N, V+N, P+N), compound adjectives formed from (A+A. N+A, V+A), and compound verbs (N+V, A+V, V +V). The type of compound that is most widely used in the novel is the endocentric compound which has the highest percentage.